KONSISTENSI PRODUKSI NATA DALAM MEDIA FERMENTASI YANG MENGANDUNG HIDROLISAT UBI KAYU (Jurnal Teknologi Industri Pertanian, 2017)
Nata de coco is known as a gelatinous substance, white to creamy-yellow, firm, glossy and not sticky, produced by some bacteria, which forms on the surface of coconut water medium during fermentation. Acetobacter xylinum (current name: Gluconacetobacter xylinus) is the common bacteria which synthesized nata de coco. Besides coconut water, there are some alternatives for making nata, such as cassava. Gluconacetobacter sp. was employed in this study to produce nata de coco from cassava hydrolysate medium (U) and compared it qualitatively and quantitatively to coconut water medium (K). In U medium, glucose was the main product derived from hydrolysis of cassava. Fermentation was conducted three times with each former fermentations became sources of inocula for the next fermentations, respectively. All data were analysed with IBM SPSS Statistics 23. Fermentation product of nata from U medium were relatively stable in thickness, wet weight, dry weight, yield, water content, and log from total bacteria (quantitative) and in colour, texture, transparency, and surface of nata (qualitative). Glucose was rapidly consumed by bacteria then other sugar (fructose and sucrose). Glucose consumption and nata yield was affected by the number of bacteria. However, nata yield was not significantly influenced by glucose consumption. Nata yield was possibly influenced by other factors such as nutrient content in U medium. Growth dynamics of Gluconacetobacter sp. was measured in log cfu mL-1 on Hassid-Barker Agar (HBA) medium and relative number of 16S rRNA genes. Bacterial growth during fermentation in U medium were relatively more stable than fermentation on K medium although the yield in K medium gradually increased and were higher than U medium. Keywords: cassava hydrolysate, Gluconacetobacter sp., nata, stable fermentation